ON NEW EXACT TRAVELING WAVE SOLUTIONS OF THE HAMILTONIAN AMPLITUDE EQUATION - Ozkan, Ayten; Ozdemir, Nagehan (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2025)
Nonlinear differential equations have an important place in mathematical physics. In this paper, the G '/G2 expansion method is used to obtain new exact traveling wave solutions of the Hamiltonian amplitude equation that arise in the analysis of various problems in fluid mechanics and theoretical physics. All calculations in this study are made using the software program and the solutions obtained are substituted in the equations. The solutions obtained have important areas of use in the fields of mathematical physics and engineering.
Keywords: Nonlinear differential equation; Hamiltonian amplitude equation; G '/G2 expansion method; DIFFERENTIAL-EQUATIONS; Science & Technology - Other Topics